Closing the immunity gap through the strategy of intensification of routine immunization using the offline tool immunogram and supportive supervision - experiences from the rural health training centre of KVG medical college, Karnataka - Holla, Narayana V.; Chivukula, Satya Kishore; Kaniambady, Sharanya (International Journal Of Community Medicine And Public Health, 2016)
Background: Since the inception of EPI in 1978, India is consistently trying to achieve and sustain high vaccination coverage. The objectives were to detect population immunity gap in the catchment area of RHTC through the offline tool - immunogram and to evolve the shortest period required for closing this gap using immunogram and supportive supervision. Methods: A short term interventional field study from December 2012 to April 2013 done in RHTC of KVG Medical College. Children born since 1st April 2010 were line-listed chronologically in the ‘immunogram’ which can both record vaccination data and measure programme indicators – hence the name. Data analyzed and baseline indicators obtained. Sustained Supportive Supervision provided was documented at the RHTC. The study ended on 31st March 2013 on clearance of the backlog coinciding with the launch of pentavalent - replacing DPT + HepB from 1st April 2013 in Karnataka. Results: RHTC is a good performing planning unit with high baseline coverage; 90% for primary vaccination. Significant impact was seen with measles 1, DPT/OPV booster dose and Measles 2nd dose which increased from 89 to 97%, 85 to 95% and 55 to 94% respectively in consecutive intensified regular sessions in 3 months. Conclusions: Immunogram precisely detected the immunity gap in a good performing planning unit and rapidly closed the gap in just 3 months, realizing the theme of WHO world immunization week 2016 – close the immunization gap. The planning unit graduated from good to better forever.